PENGARUH UKURAN PERUSAHAAN, SOLVABILITAS, PROFITABILITAS, DAN OPINI AUDIT TERHADAP AUDIT DELAY (studi empiris pada Perusahaan Pertambangan yang terdaftar pada Bursa Efek Indonesia Tahun 2014-2016) - Anggela, Anggela; Anisma, Yuneita; Rusli, Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aim determinan the effect of company size, solvability, profitability and audit opinion on audit delay on mining company listed on Indonesia Stock Exchange in 2014-2016. The samples taken in this research is 24 companies with 3 years period of research, all sum into 72 samples. Data used in this research is a secondary data which is obtained from IDX in aroud 2014- 2016 periods. The sampling technique used the purposive sampling method. Data analysis technique used the multiple regression analysis. According to the result research applied with mutple regression analysis shows there are two are variables wich significans efeect an audit delay such as the profitability and audit opinion, nevertheless the variables of company size and solvability are not impacted the audit delay. Whereas based test on the coefficient of determination (R2 ) obtained value R square of 0,661. This shows that all the independent variables efeect the dependent variable 66,1%. While the 43,9% influenced by other variable not examined in this studyKeywords : Audit Delay, Company size, Solvability, Profitability and Audit Opinion